REPRESENTAMEN CINTA DALAM KISAH NABI SULAIMAN DAN RATU SABA’ SURAT AN-NAML (Studi Analisis Semiotika dan Komunikasi Interpersonal) - Muhamad Agus Mushodiq (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2018)
AbstractThis paper aims to find the meanings of the signs which are contained in the Prophet Sulaiman and Saba’ Queen story. On the other view, this paper aims to reveal the interpersonal communication process between them that allegedly contain expression of love which ended in marriage. These meanings are analyzed using Peircean semiotics. Peircean semiotics focus of its triadic system, with the result that researcher has to pass three stages of analysis (represntament, object and interpretant) when he interpret the signs, and also this research intended to apply the interpersonal communication theory. After reading Prophet Sulaiman and Saba’ Queen story through Peircean semiotic views and interpersonal communication theory, this research finds some language symbols which are indicated love expressing. Those language symbols –among others- are the application of fiil mabni li majhul qila that implicated meaning of Sulaiman’s hospitable and friendly attitude to Queen Saba’. Direct imperative sentence without harfu nida ya’ implicate Sulaiman’s hope to feel close with Saba’ Queen.  And then, love indication that shown by Saba’ Queen is her positive response to Sulaiman’s letter. As for the Sulaiman’s feeling expression process that explained by al-Quran explicitly are (1) sensing (2) interpreting, (3) feeling, (4) intending, and (5) expressing. Whereas Saba’ Queen’s feeling expression process explained by al-Quran explicitly are (1) sensing and (2) expressing. Keywords: Representament; object; interpersonal communication; sign.